Integrated Reporting: Problems of Formation - N. A. Mislavskaya (Учёт. Анализ. Аудит)
The modern management system has a complex, sometimes multi-level organizational management structure and puts forward more and more demands on the quality of the financial information provided. The paper describes an integrated reporting that meets the increasing stakeholders demands. The research methodology is classical by itself and based on the use of situational and dialectical approaches to the object having the method of abstraction, formalization and generalization. A deductive analysis of general scientific, geopolitical factors, economic psychology, economic theory and accounting theories, projected onto the Russian specifics of doing business which leads to the formation of nontrivial conclusions. The latter are interesting in the symbiosis of criticism and constructivism because against the lack of objective reasons for the introduction of integrated reporting in Russia, there are questions raised about the need to generate a unified theory that underlies the functioning of accounting systems as well as the economic consciousness development of our society and implementation of business ethics. The scientific and practical significance of the study is to identify the application features of integrating financial reporting practice at the national level.